Proteomics Analysis Reveals the Molecular Mechanism of MoPer1 Regulating the Development and Pathogenicity of Magnaporthe oryzae - Chen, Yue; Wu, Xiyang; Chen, Chunyan; Huang, Qiang; Li, Chenggang; Zhang, Xin; Tan, Xinqiu; Zhang, Deyong; Liu, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
GPI-anchoring is a prevalent Glycosylphosphatidylinositol modification process of posttranslational protein. In our previous study，MoPer1, a GPI-anchoring essential factor, play important roles in growth, conidiogenesis and pathogenicity in M. oryzae, but the molecular mechanism is not clear. Here, we extracted the glycoproteins of the ∆Moper1 mutant and wild-type Guy11, and analyzed the difference in the expression of glycoproteins in the ∆Moper1 mutant and wild-type Guy11 by quantitative proteomic analysis of TMT markers. After background subtraction, a total of 431 proteins, with significant changes in expression, were successfully identified, these differential proteins involved in biological regulation, as well as cellular process and metabolic process, binding, catalytic activity and other aspects. Moreover, we found that MoPer1 regulates the expression of 14 proteins involved in growth, development and pathogenicity of M. oryzae. These results help us to further understand the molecular mechanism of MoPer1 regulating the growth, development and pathogenicity of M. oryzae.